On International and National Dimensions of Risk Sharing - Crucini, Mario J. (The Review of Economics and Statistics, 1999)
This paper contributes to the empirical literature that tests the implications of risk sharing across regions or countries. Rather than test the null of full insurance, the estimation method produces a parameter that measures the fraction of the annuity value of individual income that individuals of different regions (or nations) pool. Comparing the provinces of Canada, the states of the United States, and the G-7 countries, I find similar degrees of risk sharing within regions of Canada and the U.S. that exceed the risk sharing that occurs across countries. Specifically, more than two-thirds of the fitted annual variation in regional consumption is common to all regions compared to less than one-third in the case of G-7 countries.